Humanistic management, Volume II,, Foundations, cases, and exercises social entrepreneurship and mindfulness - Bachani, Jyoti; Blomme, Robert J. (Principles for responsible management education collection, 2018)
Part I. Social entrepreneurship as humanistic management -- 1. Social entrepreneurship as a form of humanistic management / Michael Pirson -- 2. Homeboy industries: stopping bullets with jobs / R. Duncan, M. Pelly, and Stephen J.J. McGuire -- 3. Harnessing the potential of gamification in humanistic management teaching: games for change / Jennifer S.A. Leigh, Erica Steckler, and Whitney Ennis -- 4. Social enterprises and the integration of persons with mental disabilities in the Greek society: a case-study of Koispe Athena-Elpis / Aikaterini Argyrou, Tineke Lambooij, Robert Blomme, and Henk Kievit -- 5. A path out of poverty: turning biowaste into opportunity at the base of the economic pyramid in Indonesia / Linda Herkenhoff and Don A. Earnest -- Part II. Practices of humanistic management -- 6. Mindfulness and humanistic management / Michael Pirson -- 7. Mindfulness through improv: the individual in a group / Jyoti Bachani -- 8. Appreciative inquiry: humanistic values at work / Niels Tekke -- Index